Telemedicine Adoption in Developing Economies: A Systematic Review on the Enablers and Barriers - Macabato, Zaidbren; Velasco, Lemuel Clark; Escabarte, Art Brian; Poblete, Mae-Lanie Ong; Isla, Armando, Jr.; Cafino, Rentor; Aquino-Cafino, Sarah Lizette; Teofilo-Orencia, Frevy (UI Scholars Hub, 2024)
Telemedicine’s adoption has been effective in certain contexts despite being controversial in certain settings because of its tendency to cause misdiagnosis and concerns about data privacy. This study aimed to synthesize the research findings on the factors leading to the adoption of telemedicine among developing economies. The study utilized Preferred Reporting Items for Systematic Reviews and Meta-Analysis methodology to analyze 27 related literature and the Unified Theory of Acceptance and Use of Technology to map out the factors considered enablers and barriers in adopting telemedicine. Results showed that performance expectancy, effort expectancy, social influence, and facilitating conditions were significant predictors. However, the study also underscored that the lack of information and communications technology support, lack of resources, lack of organizational effectiveness, lack of quality care, lack of motivation, lack of trustworthiness, and lack of user satisfaction were predominant hindrances at both individual and organizational levels. This analysis on the enablers and barriers of telemedicine adoption hopes to contribute strategic recommendations that practitioners in public health, decision-makers in global health policy, technology developers, and future research may explore to expand the existing knowledge on the optimal adoption of telemedicine in developing economies.